Hierarchy and value comparative perspectives on moral order - Hickel, Jason 1982-; Haynes, Naomi (Studies in social analysis, 2018)
Globalization promised to bring about a golden age of liberal individualism, breaking down hierarchies of kinship, caste, and gender around the world and freeing people to express their true, authentic agency. But in some places globalization has spurred the emergence of new forms of hierarchy-or the reemergence of old forms-as people try to reconstitute an imagined past of stable moral order. This is evident from the Islamic revival in the Middle East to visions of the 1950s family among conservatives in the United States. Why does this happen and how do we make sense of this phenomenon? Why do some communities see hierarchy as desireable? In this book, leading anthropologists draw on insightful ethnographic case studies from around the world to address these trends. Together, they develop a theory of hierarchy that treats it both as a relational form and a framework for organizing ideas about the social good